Earthquake Statistical Parameters Analysis and Regional Variations of March 02, 2017 Adıyaman-Samsat Earthquake (Ml = 5.7) by Using its Aftershocks - Nihan HOSKAN (Doğal Afetler ve Çevre Dergisi)
In this study, using the aftershocks that occurred after the March 02, 2017 Adıyaman-Samsat Earthquake (Ml = 5.7) statistical analyzes of b-value and aftershock decay parameter p-value were performed. 1345 aftershocks compiled from the catalogs of the Kandilli Observatory and Earthquake Research Institute (KOERI) and the Disaster & Emergency Management Authority (AFAD) were homogenized according to the local magnitude Ml. Afterwards, the completeness magnitude Mc=1.6 was obtained with the moving time window approach and using maximum likelihood method, b-value was calculated as 0.768±0.03 for the whole region. This value is close to the expected 1 for b for tectonic earthquakes and is consistent with the Gutenberg-Richter relation. With modified Omori's Law p=0.91±0.05, c=0.041±0.030 and K=25.6±3.21 were calculated for the entire region. The p-value, which is thought to be related to crustal heterogeneity, heat flux and tectonic deformation, is less than 1, reflecting the relatively slow aftershock decay rate. Regional variation maps of b- and p-parameters were prepared by taking 450 earthquakes at each node point with 0.01O x 0.01O grid interval. The b-value was high in the northeast-southwest line of the March 02, 2017 (Ml=5.7) earthquake and low in the south-southeast of this earthquake. Besides the low b-value, the occurrence of the 24 April 2018 (Ml=5.4) earthquake in the region may foreshadow the increase in regional stress. Examining the regional variation of the p-value, the high p-value is in the north-northeast of the Adıyaman-Samsat earthquake and is almost consistent with the deformation region on the InSAR map given in literature.